Preparation and Characterization of Immobilized Valproic acid onto Tetraethyl Orthosilicate - Ahmed Haroun; Ragab A. Masoud; Ali H. M. Osman (Journal of Sustainable Materials Processing and Management, 2024)
This work aims to preparation and characterization of xerogel by co-gelation of tetraethyl orthosilicate (TEOS) and 2-propylpentanoic acid (Valproic acid, VA). To characterize the resultant material, infrared spectroscopy (FT-IR), X-ray diffraction (XRD), scanning and transmitting electron microscopes (SEM and TEM) were applied. In addition, the in vitro VA release and kinetic of released using the different mathematical models (zero-order, first-order and Higuchi) were carried out in a phosphate buffer pH 7.4 at37°C using HPLC. The FTIR, XRD results confirmed the successful preparation of the xerogel with an amorphous structure. However, TEM images revealed a spherical-like morphology with an average size of about 1910 d.nm compared to the pure TEOS 924 d.nm. The study also demonstrated controlled VA release after 4 h, showing that xerogel based on TEOS is a promising VA delivery technology with sustained release that followed the Higuchi kinetic throughout 24 h.